PENGETAHUAN ILMIAH DAN KEBENARAN DALAM ILMU KOMUNIKASI - Mukhtar Effendi (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2012)
Human beings have a high curiousity that leads them to produce knowledge that willhelp them to solve their problems. Their curiousity continues to exist although they have beenable to solve their problem. Through this process, the production and reproduction ofknowledge continues to exist.From the academic perspective, the answer to the curiousity of human beings areaccepted and acknowledged when it is scientifically accepted. This leads to determine the trueand false knowledge. The true knowledge are achieved when it has scientific standards ofknowledge.This article discussed the scientific truth in knowledge, especially communicationstudy which is developing rapidly. As a new science, communication study has some criteriaand measurement of truth which have some differences with other social sciences. However,communication study is really a part of social science that makes human being as its mainstudy.